Analyzing Association between Gender Centricity and Media Literacy (Journal of Advanced Research in Journalism & Mass Communication, 2020)
UNDP has laid down clear sustainable development goals for the world to pursue and achieveto make it a better place to live. One such SDG (Sustainable Development Goal) is gender equality. There are many efforts being put in the world to achieve this goal and media has been playing a pivotal role by strengthening these efforts time to time. The recent rise of social media has further provided voice to the voiceless by highlighting the gender specific issues and sending it across to the billions of timelines in moments. With the rise, popularity and greater engagement of the people with the various media forms, knowing the levels of awareness of gender issues among the media users is of paramount importance. The objective of this research effort was to find out the association of the gender centricity and the extent of media literacy. The study was conducted on the college-going students of various state, central and private universities located in and around Delhi. Questionnaire was used as the tool for primary data collection and SPSS software as the data analysis tool. The findings suggested a weak association between the extent of media engagement and the gender centricity of the respondents. ‘Gender Centricity’ here has been referred to the actions of the respondents post consumption of media content for the purpose of this research. It also suggested that the university setup of the students played a decisive role in determining their response towards gender centric media content and their degree of gender centricity exhibited through their actions. How to cite this article: Pandey PK, Pathak CC. Analyzing Association between Gender Centricity and Media Literacy. J Adv Res Jrnl Mass Comm 2019; 6(3): 10-13. DOI: https://doi.org/10.24321/2395.3810.201905